Pre-treatment Effects of Eriobotrya Japonica Extraction on Malondialdehyde (MDA), Brain-Derived Neurotrophic Factor (BDNF), and Superoxide Dismutase (SOD) Levels in Hippocampus of Parkinsonian Rats Induced by 6-hydroxydopamine Following 12 weeks of Volunt - Zia Fallah Mohammadi; Razieh Mohammadi; Jalil Aslani (مجله دانشکده پزشکی اصفهان, 2014)
Background: The purpose of this study was to investigate the effects of extract of Eriobotrya japonica flower on brain-derived neurotrophic factor (BDNF), superoxide dismutase (SOD), and malondialdehyde (MDA) levels in the hippocampus of Parkinsonian rats after 12 weeks of voluntary exercise on a running wheel.